Transonic Buffet Effects on Shockwave-Induced Lift Stress Response and Fatigue Life of the SC(2)-0714 Supercritical - Budi Aji Warsiyanto; Riskha Agustianingsih (Jurnal Teknologi Kedirgantaraan, 2025)
Transonic buffet, triggered by shockwave–boundary layer interaction, produces oscillations that cause unsteady lift fluctuations, structural stresses, and accelerated fatigue damage. Understanding this chain—from shockwave to lift, stress, and fatigue—is critical for the durability of modern aircraft wings, especially those employing supercritical airfoils. This study investigates the SC(2)-0714 supercritical airfoil using CFD in ANSYS Fluent at Mach 0.8 with AoA 2°, 4°, and 6°, combined with structural and fatigue analysis in Abaqus and Fe-Safe. Results show stress levels between 1.26 and 12.6 MPa, well below the yield strength of Al 2024-T3, confirming safe static margins. However, fatigue life declined sharply with AoA, from 177,868 cycles at 2° to 130,282 cycles at 6°. These findings emphasize that while stresses remain within limits, transonic buffet–induced lift fluctuations critically reduce fatigue life, underscoring the urgency of incorporating buffet effects into structural durability assessments and airfoil design.